Social-Emotional Learning and Academic Achievement - Meghan P. McCormick; Elise Cappella; Erin E. O'Connor; Sandee G. McClowry (SAGE Publishing, 2015)
Social-emotional learning (SEL) programs have demonstrated positive effects on children's social-emotional, behavioral, and academic outcomes, as well as classroom climate. Some programs also theorize that program impacts on children's outcomes will be partially explained by improvements in classroom social processes, namely classroom emotional support and organization. Yet there is little empirical evidence for this hypothesis. Using data from the evaluation of the SEL program INSIGHTS , this article tests whether assignment to INSIGHTS improved low-income kindergarten and first grade students' math and reading achievement by first enhancing classroom emotional support and organization. Multilevel regression analyses, instrumental variables estimation, and inverse probability of treatment weighting (IPTW) were used to conduct quantitative analyses. Across methods, the impact of INSIGHTS on math and reading achievement in first grade was partially explained by gains in both classroom emotional support and organization. The IPTW method revealed that the program impact on reading achievement in first grade was partially explained through an improvement in classroom organization. Implications for research and practice are discussed.